2022
DOI: 10.3390/cells11071130
|View full text |Cite
|
Sign up to set email alerts
|

ROCK ‘n TOR: An Outlook on Keratinocyte Stem Cell Expansion in Regenerative Medicine via Protein Kinase Inhibition

Abstract: Keratinocyte stem cells play a fundamental role in homeostasis and repair of stratified epithelial tissues. Transplantation of cultured keratinocytes autografts provides a landmark example of successful cellular therapies by restoring durable integrity in stratified epithelia lost to devastating tissue conditions. Despite the overall success of such procedures, failures still occur in case of paucity of cultured stem cells in therapeutic grafts. Strategies aiming at a further amplification of stem cells during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 153 publications
0
9
0
Order By: Relevance
“…However, ROCK inhibitors have now been recognized as useful tools to promote the survival of multiple types of stem cells. 39 …”
Section: Discussionmentioning
confidence: 99%
“…However, ROCK inhibitors have now been recognized as useful tools to promote the survival of multiple types of stem cells. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that negative regulation of Rock1 by miR-148a may maintain the selfrenewal and stemness characteristics of HF-SCs, which has been observed in primary skin tissue cultures after inhibition of Rock1 (An et al, 2018). In addition, studies have suggested that Rock1 signalling inhibition elevates stem/progenitor cell functions, in vitro (Centonze et al, 2022). Furthermore, Rock1 has been shown to promote embryonic SC-colony formation and maintenance of neural progenitor cells (Chang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Rock1 has been shown to be involved in proliferation and differentiation processes of keratinocytes and in other epithelial cells (Ma et al, 2017). In addition, reduced Rock1 function results in cellular senescence, both in vitro and in vivo (Centonze et al, 2022;Kümper et al, 2016). This loss of Rock1 mediated cellular senescence involves downregulation of cell cycle protein Cdk1 (Diril et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that negative regulation of Rock1 by miR-148a may maintain the self-renewal and stemness characteristics of HF SCs, which have been observed in primary skin tissue cultures after inhibition of ROCK1 (An et al, 2018). In addition, studies have suggested that ROCK1 signaling inhibition elevates stem/progenitor cell functions, in vitro (Centonze et al, 2022). Furthermore, ROCK1 has been shown to promote embryonic SC colony formation and maintenance of neural progenitor cells (Chang et al, 2010), whereas Elf5 is expressed in differentiated epidermal and oral mouse KCs as well as in the inner root sheath and outer root sheath of HFs (Choi et al, 2008;Oakes et al, 2008;Parikh et al, 2008;Singh et al, 2019;Tummala and Sinha, 2006).…”
Section: Discussionmentioning
confidence: 99%